Operando XAS/SAXS: Guiding Design of Single‐Atom and Subnanocluster Catalysts. Issue 5 (12th February 2021) - Fang, Lingzhe; Seifert, Soenke; Winans, Randall E.; Li, Tao
Abstract: Single‐atom and subnanocluster catalysts (SSCs) represent a highly promising class of low‐cost materials with high catalytic activity and high atom‐utilization efficiency. However, SSCs are susceptible to undergo restructuring during the reactions. Exploring the active sites of catalysts through in situ characterization techniques plays a critical role in studying reaction mechanism and guiding the design of optimum catalysts. In situ X‐ray absorption spectroscopy/small‐angle X‐ray scattering (XAS/SAXS) is promising and widely used for monitoring electronic structure, atomic configuration, and size changes of SSCs during real‐time working conditions. Unfortunately, there is no detailed summary of XAS/SAXS characterization results of SSCs. The recent advances in applying in situ XAS/SAXS to SSCs are thoroughly summarized in this review, including the atomic structure and oxidation state variations under open circuit and realistic reaction conditions. Furthermore, the reversible transformation of single‐atom catalysts (SACs) to subnanoclusters/nanoparticles and the application of in situ XAS/SAXS in subnanoclusters are discussed. Finally, the outlooks in modulating the SSCs and developing operando XAS/SAXS for SSCs are highlighted. Abstract : Operando X‐ray absorption spectroscopy is wildly used to monitor the oxidation state and atomic structure changes of single‐atom catalysts during working conditions. Considering the transformation of single‐atoms to clusters under high temperature or applied potential, combining operando small‐angle X‐ray scattering, to capture the size, and valence variation simultaneously is essential.